The art of colour : the history of art in 39 pigments. - Grovier, Kelly (London : Thames and Hudson, 2023)
"Invented by Stone Age cave-dwellers and medieval conjurers, cunning conmen and savvy scientists, the colours of art tell a riveting tale all their own. Over ten scintillating chapters, acclaimed author Kelly Grovier brings that tale vividly to life, revealing the astonishing backstories in the history of art. Interwoven between these chapters is a series of features focusing on key moments in the evolution of colour theory - from the revelations of the Enlightenment to the radicalism of the Bauhaus - while reproductions of more than 100 carefully selected artworks help illuminate the narrative's twists and turns. The history of colour is an epic saga of human ingenuity and insatiable desire. Read this book and you will never look at a work of art in the same way again" -- Provided by publisher
Introduction: artymology -- Red. Red ochre; Carmine; Rose madder; Vermilion; Red lead -- Orange. Orpiment; Saffron; Chrome orange; Cadmium orange -- Yellow. Yellow ochre; Lead-tin yellow; Naples yellow; Indian yellow; Chrome yellow; Cadmium yellow; Arylide yellow -- Green. Verdigris; Malachite; Emerald green; Viridian -- Blue. Azurite; Ultramarine; Cobalt blue; Cerulean; Prussian blue; Artificial ultramarine; International klein blue -- Purple. Tyrian purple; Maeve; Cobalt violet -- Black. Charcoal; Bone black -- White. Lead white; Calcite; Kaolin -- Brown. Umber; Van Dyke brown; Excrement -- Precious metals. Gold; Silver.
boek